Food insecurity in American suburbs : lived experiences in the Bonney Lake area, Washington, USA - Bear, B (2015)
Suburban spaces within the United States have been subject to change over the past 50 years, in part because of the suburbanization of poverty. Suburban poor live within a policy blindspot. As result, increasing poverty within these areas has not received deserved attentions, leaving their challenges unaddressed. This thesis will use a case study of the Bonney Lake area in Washington, USA, to discuss challenges associated with living in suburban space and suburban poverty on issues of suburban food security. This will involve examination of shopping practice and motivations, in addition to issues of accessibility, choice, and affordability within the area, including the use of efficiency and nutrition shopping practice, influences of culture’s entanglement with familiarity, influences of the management effect, and the use of thrift, treats, and self-sacrifice. It finds time and transportation to be two important factors of food security within the Bonney Lake area.